Controller Synthesis of Time Petri Nets Using Stopwatch - Parisa Heidari; Hanifa Boucheneb (Journal of Engineering)
Scheduling is often a difficult task specially in complex systems. Few tools are targeted at both modeling and scheduling of the systems. In controller synthesis, a scheduler is seen as a controller to manage shared resources and timing requirements of a system. This paper proposes a time Petri net-based approach for controller synthesis and finding a scheduler using stopwatch. The solution suggested here is particularly interesting for preemptive scheduling purposes. This paper deals with time Petri nets with controllable and uncontrollable transitions and assumes that a controllable transition can be suspended and retrieved when necessary. In fact, the paper supposes that every controllable transition can be associated with stopwatch. With this hypothesis, the objective is to model a system by time Petri nets and calculate subintervals where the system violates the given property. Then, the controller associates the corresponding controllable transitions with stopwatch to suspend them in their bad subintervals. The interesting advantage of this solution is that this approach synthesizes an ordinary time Petri net model before adding stopwatch. Therefore, complicated computations and overapproximations required during controller synthesis of time Petri nets associated with stopwatch are avoided.